Enterprise Architecture As An Enabler Of Digital Transformation In The Government Sector: Success Factors And Maturity Evaluation Methodology - Erni Juraida; Dana Indra Sensuse (Green Publisher Indonesia, 2024)
Enterprise Architecture (EA) plays an important role as an enabler of digital transformation with strategic objectives, especially in digital government initiatives. Despite its potential, EA implementation in the public sector faces challenges such as complex organizational structures, diverse stakeholder interests, and regulatory constraints. This study aims to systematically review the literature to identify critical success factors that influence the success of EA implementation in government and propose a comprehensive maturity evaluation methodology. Using a systematic literature review of 48 studies published between 2018 and 2024, this research identifies key factors such as strategic alignment, governance, human resource capabilities, and stakeholder engagement as critical to achieving effective EA implementation. It also introduces an EA maturity evaluation model designed for the public sector to assess and improve EA practices. The citizen-centric aspect is the novelty of this research where the factors in this aspect characterize the implementation of EA in the digital government sector. The findings provide insights and academic contributions in expanding the study of EA in the public sector as well as providing practical guidance for government agencies to improve their EA maturity so that accelerated digital transformation can be achieved